Hava Trafik Kontrolünde Kontrolör Kararları Nedeni İle Oluşan Gecikmelerin Analizi - Eren, Utku (Fen Bilimleri Enstitüsü, 2013)
Bu çalışmada iki farklı veri seti kullanılarak, Avrupa Hava Sahası üzerinde bir takım analizler gerçekleştirilmiş ve bu hava sahasını modelleme yöntemlerinin verimliliği üzerinde durulmuştur. Öncelikle, Hava Trafiği modellerine ön ayak olması amacı ile Avrupa Hava Sahası üzerinde bulunan hava alanlarının ve hava limanlarının ayrı ayrı bağlantı grafları analizler için kullanılan veri setleri üzerinden oluşturulmuş ve trafik akışının karakteristikleri hakkında bilgi edinmek amacı ile Fransa Hava Sahası incelenmiştir. Bu noktadan sonra gecikme analizlerine geçilmiş ve yaşanan gecikmeler iki farklı bakış açısı ile incelenmiştir. İlk olarak her uçuş için uçuşun geçtiği tüm hava alanları üzerinde yaşadığı gecikmeler gerçek uçulan ve planlanan sürelerin farkı ile hesaplanmış ve uçuşun bütün fazlarındaki yaşadığı gecikmeler elde edilmiştir. Bütün uçuşların sonuçlarının birleştirilmesi üzerine, Avrupa hava sahası üzerindeki gecikme üretim dağılımları ve bu dağılımların zamanla nasıl ilerlediği elde edilmiş, gecikme üretimi açısından sorunlu bölgeler saptanmıştır. İkinci bir yaklaşım olarak hava limanları ağı üzerinde gecikmelerin nasıl ilerlediği araştırılmış ve farklı bir modelleme yöntemi önerilmiştir. Bu metodun hava limanları arasında gerçekleşen tüm uçuşları ayrı ayrı incelemesi nedeni ile temsil etme kapasitesi daha yüksek bir modelleme yöntemi olduğu sonucuna varılmıştır.

In this study by using two different sets of data, analyses have been conducted over European Airspace and the efficiencies for modelling techniques of European Air Traffic Network are investigated. Before all else, in order to be the initiator of an air traffic model of European Airspace, connectivity graphs of both airspaces and airports have been generated directly via utilization of data sets. To be able to have an insight about air traffic flow patterns and characteristics France Airspaces have been analyzed. From that point on, delay propagation analyses have been conducted and delays have been investigated with two different approach. Firstly, for every flight, delay of each crossed airspace has been calculated by seeking the difference between planned and actual data. Aggregation of all these delay data from every flight resulted with the distribution of delay generations across the whole European Airspace. Moreover, utilizing this method in a long time interval yielded the propagation of delays through time and gathering all these results together pointed out the congested regions with generally and/or highly delay generating regions. As a secondary modelling approach, analyses have been conducted over the connectivity graph of airports. All flights between each airport pair have been investigated along with airport analyses implemented with all flights regarding those airports. It has been observed that the second approach provides a more representative modelling method because it compares the flights between airport pairs with all other flights which gives more inferences for the reasons of delays and their propagations.
Analysis Of Generated Delays Due To Air Traffic Control Decisions In Air Traffic Management
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2013
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2013
Keywords: Hava Trafik Kontrolü; Hava Trafik Yönetimi; Gecikme Analizleri; Avrupa Hava Trafiği Modelleri; Gecikme Yayılma Modelleri; Air Traffic Control; Air Traffic Management; Delay Analyses; European Air Traffic Models; Delay Propagation Models